Manajemen Digitalisasi Sekolah di Sekolah Dasar Negeri 2 Patukangan Kabupaten Kendal - Hadiyanto, Pujo; Nurkolis, Nurkolis; Haryati, Titik (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
Abstract The context of this research is SDN 2 Patukangan which has advantages in school digitalization management regarding the Ministry of Education and Culture's platforms and applications including: School Activity Plan and Budget Application (ARKAS), Educational Report Cards, School Procurement Information System (SIPLah), Data Based Planning (PBD), TanyaBOS, e-Kinerja, Merdeka Mengajar Platform (PMM). This success certainly cannot be separated from the role of the Principal, School Committee, Teachers' Council, and related departments as well as the environment which collaborates in a collaborative effort process to achieve the school's vision, mission and goals effectively and efficiently. The aim of this research is to find out information in depth and describe: planning, organizing, implementing and supervising school digitalization management. This research used a qualitative approach with descriptive phenomenological methods which was carried out in November-August 2024 at SD Negeri 2 Patukangan, Kendal District, Kendal Regency by obtaining data through observation, documentation and interviews. The data analysis technique used is the iterative model from Miles and Huberman, namely: data collection, data reduction, data presentation and drawing conclusions. Checking the validity of the data uses credibility, transferability, dependability and confirmability tests. The results of the research show that (1) planning for the digitalization of school management, preparing school work programs: annual activity plans and school budget activity plans in accordance with the educational report card profile through data-based planning by means of identification, reflection and improvement (2) organizing the digitalization of school management by dividing and assignments according to their competencies. (3) implementation of digitalization of ARKAS school management updated to the latest version, procurement of goods and services through SIPLah, e-Kinerja through the Merdeka Mengajar Platform, teachers getting certificates from PMM. (4) supervision of the digitalization of school management, seen from the results of monitoring and evaluation from the school principal and from related agencies. Based on the results of the research that has been carried out, it can be concluded that the success of school digitalization management is based on scheduled and detailed planning, organized with good communication, cooperation and collaboration according to their duties and competencies, carried out with high commitment, carried out comprehensive and detailed supervision by the principal in completing tasks and obligations, as well as monitoring and evaluation by the relevant Department. Keywords: Digitalization, Planning, Based, Application, Platform